Global Economic Prospects, June 2013 : Less Volatile, but Slower Growth - World Bank (Washington, DC, 2013)
The global economy appears to be transitioning toward a more stable period. Although acute risks have diminished, real-side activity remains sluggish – especially in high-income Europe. Most developing countries have fully recovered from the crisis. Although growth is slower than during the boom period, it is in line with underlying potential, and output is projected to pick up only gradually to around 5.8 percent by 2015. High unemployment and spare capacity remain pressing problems in developing Europe and the Middle East and North Africa. With a more stable external environment, new risks and challenges are gaining prominence, including the potential impact on exporting countries of a faster than anticipated decline in commodity prices, the possibility that the eventual withdrawal of quantitative easing exposes vulnerabilities in developing countries, and the need to resort increasingly to supply-side rather than demand stimulus policies to achieve stronger growth.